Update Breast Cancer 2021 Part 1 – Prevention and Early Stages - Stickeler, Elmar; Aktas, Bahriye; Behrens, Annika; Belleville, Erik; Ditsch, Nina; Fasching, Peter A.; Fehm, Tanja N.; Hartkopf, Andreas D.; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lüftner, Diana; Lux, Michael P.; Müller, Volkmar; Schneeweiss, Andreas; Schütz, Florian; Schulmeyer, Carla E.; Tesch, Hans; Thomssen, Christoph; Uleer, Christoph; Untch, Michael; Welslau, Manfred; Wöckel, Achim; Wurmthaler, Lena A.; Würstlein, Rachel; Thill, Marc (Geburtshilfe und Frauenheilkunde, 2021)
This review summarises not only the latest evidence on prevention, but also the current research on the treatment of early-stage breast cancer patients. Recent years have seen a growing body of evidence on the risk of high- and moderate-penetrance breast cancer susceptibility genes. A large international consortium has now been able to further refine the answer to the question of the significance of the so-called panel genes. Moreover, the data on treatment selection regarding endocrine efficacy and the decision for or against chemotherapy have also been advanced markedly. There is also new data on adjuvant CDK4/6 (cyclin-dependent kinase 4/6) inhibitors, which are standard in first-line treatment in patients with metastatic HER2-negative, hormone receptor-positive (HR+) breast cancer. For other therapies such as immune checkpoint inhibitors, which have successfully improved the rate of pathologic complete response (pCR) in neoadjuvant treatment settings for patients with triple-negative breast cancer (TNBC), there is a growing understanding of the quality of life and side effects. This is especially important in situations where patients could possibly be cured without such a regimen.In dieser Übersichtsarbeit werden nicht nur die neuesten Erkenntnisse zur Prävention, sondern auch die aktuellen Arbeiten zur Behandlung von Mammakarzinompatientinnen im frühen Krankheitsstadium zusammengefasst. In den letzten Jahren haben sich die Hinweise über hoch-penetrante und mittelgradig penetrante Risikogene für ein Mammakarzinom verdichtet. Nun konnte in einem großen internationalen Konsortium die Antwort auf die Frage nach der Wertigkeit der sogenannten Panelgene weiterentwickelt werden. Des weiteren sind auch die Daten zur Therapieselektion in Bezug auf endokrine Wirksamkeit und die Entscheidung für oder gegen eine Chemotherapie deutlich weiterentwickelt worden. Ebenso gibt es neue Daten zum adjuvanten Einsatz von CDK4/6-(Cyclin-dependent-kinase-4/6-)Inhibitoren, die in der 1. Therapielinie für Patientinnen mit metastasiertem HER2-negativem, hormonrezeptorpositiven (HR+) Mammakarzinom zum Therapiestandard gehören. Bei anderen Therapien wie den Immuncheckpoint-Inhibitoren, welche erfolgreich in der neoadjuvanten Therapiesituation bei Patientinnen mit einem triple-negativen Mammakarzinom (TNBC) die Rate an pathologischen Komplettremissionen (pCR) verbessern konnten, wächst das Verständnis für Lebensqualität und Nebenwirkungen. Dies ist von besonderer Bedeutung in einer Situation, in der Patientinnen potenziell auch ohne eine solche Therapie geheilt werden könnten.
Keywords: early breast cancer; prevention; treatment; prognosis; immunotherapy; digital medicine